A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey - Karakurt İbrahi̇m; Sevsay Sevgi̇; Buğa, Evren (Zootaxa, 2016)
The genus Gonothrombium is reassessed, Gonothrombium oudemansianum (Feider, 1948) redescribed and Gonothrombium ozkani sp. nov. described. All larvae were obtained by experimental rearing from field-collected females. A key to species, for adults and larvae, is provided. The distribution of the genus, hitherto known from Africa and Romania, is extended to the territory of Turkey.